The impact of the coronavirus on global higher education - Quacquarelli, Nunzio (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2020)
The global higher education landscape has dramatically changed in the past few months due to the spread of the coronavirus (otherwise known as COVID-19).